Craniostenosis - X-Ray Presentation - Babić, Rade R.; Stanković-Babić, Gordana; Babić, Strahinja; Babić, Katarina; Babić, Nevena; Jevremović, Aleksandar (Medical Word, 2024)
Craniosynostosis are a congenital condition characterized by a deformed skull, caused by the premature fusion of one or more, and exceptionally all sutures. Crouzon’s and Apert’s syndromes are classified as craniosynostosis. Along with craniosynostosis, deformities can also occur on other bones of the skeleton.The goal of the presentation is a revue and illustrative presentation of craniosynostosis.The results of the work: oxycephalus, scaphocephalia, triginocephalia, plagiocephalia, dysostosis cranio-facialis (Crouson), acro-cephalo-syndactylis (Apert) are presented.The authors conclude that radiological images of craniosynostosis have their own specificity, while radiological examination methods are relevant and irreplaceable in diagnosing craniosynostosis.
Keywords: craniosynostosis; radiology; ophthalmology; Crouzon; Apert; syndrome